CD4(+) T Lymphocytes are Not Necessary for the Acute Rejection of Vascularized Mouse Lung Transplants - Gelman, Andrew E. (2008)
Acute rejection continues to present a major obstacle to successful lung transplantation. While CD4(+) T lymphocytes are critical for the rejection of some solid organ grafts the role of CD4(+) T cells in the rejection of lung allografts is largely unknown. In this study we demonstrate in a novel model of orthotopic vascularized mouse lung transplantation that acute rejection of lung allografts is independent of CD4(+) T cell-mediated allorecognition pathways. CD4(+) T cell-independent rejection occurs in the absence of donor-derived graft-resident hematopoietic antigen presenting cells. Furthermore, blockade of the CD28/B7 costimulatory pathways attenuates acute lung allograft rejection in the absence of CD4(+) T cells, but does not delay acute rejection when CD4(+) T cells are present. Our results provide new mechanistic insight into the acute rejection of lung allografts and highlight the importance of identifying differences in pathways that regulate the rejection of various organs.